Ancestralidade e ressignificação identitária em Um rio chamado tempo, uma casa chamada terra, de Mia Couto - Lino, Maria da Conceição Gonzaga de Resende (2022)
The dialogue between history and literature makes it possible to understand the events that mark society and its culture and, in the context of literatures of African origin, leads to a reflection on the diaspora, which, according to sociologist and cultural theorist, Stuart Hall (2003), refers to issues of misery and the search for opportunities that end up disintegrating identity due to the loss of matrix contact. Notwithstanding the loss of matrix contact, by elevating himself as a voice in the social, historical and cultural sense according to Paul Zumhtor's perspective, the subject recovers it, since he becomes the voice of the individual and the collective, thus reconnecting himself , with their ancestry. It is in this direction that the work A river called time, a house called earth, by the Mozambican writer, Mia Couto, walks, in view of the diasporic issue present in the voice of the character Marianinho. Based on such considerations, the objective was to understand how the character's identity resignification was configured, insofar as his displacement implied a return to his roots and, therefore, to his ancestry. In this perspective, the research methodology, based on the literature review, mobilized the concepts of diaspora, from Stuart Hall (2003), orality and voice, in Paul Zumthor (1997, 2005) and Laura Padilha (2007); of experience and memory, based on Walter Benjamin (1987); and allegory, also from Walter Benjamin (1984), which were applied to fragments of the narrative, considering the oral marks in the written text. This research was justified, as it allowed us to reflect on narratives as cultural expressions of the diaspora, as this study made it possible to understand cultural hybridization and identity issues, which were noted in the analyzed work. We related the proposed objectives with the fragments of the narrative presented and analyzed based on the listed concepts, focusing on the theme of the diaspora as a redefinition of identity, which enabled us to perceive that these were achieved, as we verified that the linguistic elements, especially the oral marks present in the narrative, corroborated Marianinho's identity resignification, whose voice was raised as ancestry. About the problem that guided the present research, we believe that Marianinho's displacement corroborates his identity, and in this sense, his ancestry, in view of the letters received by his grandfather Dito Mariano that, when read during his return to the village, take him to reconstruct its history, in which those of the people of Luar do Chão are intertwined. Thus, we confirmed the hypothesis about the awareness that Marianinho had never left his roots and thus, the collective and the individual, as well as the past and the present, which were outlining and confirming his identity. In view of this, we believe that we have contributed to the research of contemporary scholars who focus on the subject, in order to reiterate the importance of the voice in the historical, social and cultural perspective, taking into account the experience, the construction and preservation of memory, and in this sense of identity.